Islamic integrated education system model in the Malay archipelago: implications for educational leadership - Othman, Azam; Hussien, Suhailah; Sheikh Ahmad, Ismail; Abd Rashid, Adnan; Badzis, Mastura (IIUM Press, 2017)
This paper discusses the practice of the Islamic Integrated Education System model in selected schools in the Malay Archipelago in the context of education in the 21st century. Islamic Integrated Schools provide an educational system that integrates academic knowledge and Islamic knowledge. Despite having a similar aim,these schools often have their own Islamic Integrated education system in place, which varies from school to school. An instrument derived from an earlier study conducted by this research team was utilised in the data collection process. The questionnaire focused on four constructs that describe a model of an Islamic Integrated school, that is, The School’s Concept, The Integration of Islamic and Academic Knowledge, Teacher-Student Relationship, and The School’s Islamic Climate. The sample consisted 2017of 507 students from one Singaporean, two Indonesian, and three Malaysian Islamic Integrated Schools. Overall, the model suggests that the Integration of the Islamic and Academic Knowledge was the weakest contributing factor to the overall concept of the Islamic Integrated education system compared to Teacher-Student Relationship and the School’s Islamic Climate. The findings indicate the need for the Islamic Integrated Schools to critically evaluate their existing implementation of knowledge integration to better prepare their students for the challenges of the 21st century.